PENGARUH SUPPORTING ENVIRONMENTAL PROTECTION DAN GREEN IDENTIFICATION PRODUCT TERHADAP KEPUTUSAN PEMBELIAN GREEN PRODUCT PADA MAHASISWA - Baso Agus Salim; Agustina Mutia; Ahmad Syukron Prasaja (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The primary concern of society today is the increasing amount of plastic waste. Indonesia is facing a serious problem in handling this waste, primarily due to its growing population. Indonesians tend to heavily rely on plastic products in their daily lives, and this plastic usage contributes to the rising amount of plastic waste. This highlights a significant issue in maintaining environmental sustainability in Indonesia, particularly in the province of Jambi. As the vanguard of environmental conservation efforts, students must possess awareness in safeguarding the environment. Environmental issues become even more worrisome when society cannot change its behavior to improve the situation. Therefore, there is a need to enhance supporting environmental protection as an effort to provide environmental protection and use environmentally friendly products known as green products. This research aims to determine and analyze the influence of supporting environmental protection and green product identification on the purchasing decisions of green products. The data collection method used is quantitative, with data analysis through the Determinant Coefficient test. A sample of 97 respondents was selected using the Stratified Random Sampling technique. This study employs statistical analysis. The simultaneous results of the research indicate that both supporting environmental protection and green product identification have a positive and significant influence on purchasing decisions. The coefficient of determination calculation shows that the variables supporting environmental protection and green product identification collectively influence 50.1% of the outcome, while the remaining 49.9% is affected by variables outside the scope of this study.